2020
DOI: 10.1101/2020.12.22.20248657
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adenovirus and RNA-based COVID-19 vaccines: perceptions and acceptance among healthcare workers

Abstract: ObjectivesThe aim of this study was to compare the perception, confidence, hesitancy, and acceptance rate of various COVID-19 vaccine types among healthcare workers (HCWs) in Saudi Arabia, a nation with MERS-CoV experience.DesignNational cross-sectional, pilot-validated questionnaire.SettingOnline, self-administered questionnaire among HCWs.ParticipantsA total of 2,007 HCWs working in the Kingdom of Saudi Arabia participated; 75.3% completed the survey and were included in the analysis.InterventionData were co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The lowest acceptance rate of the general population was recorded in Lebanon (21.4%) [54] , while the highest was reported by a survey conducted in Iraq (61.7%) [55] . One Saudi Arabian survey assessed the preferences of healthcare workers regarding the type of vaccine, and it found that out of all surveyed healthcare workers only 20% or 24% preferred to receive the AstraZeneca or the Pfizer vaccine, respectively, while much more declared themselves as “maybe” willing to receive them [56] . It should be noted that surveys that included healthcare professionals/workers report higher intention to receive the vaccine, compared with the general population, even in this region of the world.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest acceptance rate of the general population was recorded in Lebanon (21.4%) [54] , while the highest was reported by a survey conducted in Iraq (61.7%) [55] . One Saudi Arabian survey assessed the preferences of healthcare workers regarding the type of vaccine, and it found that out of all surveyed healthcare workers only 20% or 24% preferred to receive the AstraZeneca or the Pfizer vaccine, respectively, while much more declared themselves as “maybe” willing to receive them [56] . It should be noted that surveys that included healthcare professionals/workers report higher intention to receive the vaccine, compared with the general population, even in this region of the world.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, given that the current vaccines on the market differ drastically by their mechanism(s) of action (e.g., mRNA-based vaccines vs. genetically engineered pathogens), the different mechanism in which a vaccine work may have influenced people's opinion on it and hence hesitancy levels. Our systematic review does not address hesitancy differences specifically based on the differences in how current vaccines work, however, our systematic search did identify several studies that addressed people's preferences over different vaccine candidates [ 56 , 133 ]. Additionally, our systematic review identified the information regarding vaccine's safety and efficacy as the main barriers/motivators determining peoples’ willingness to vaccinate, and although one Denmark survey observed a decrease in the perception of Astra Zeneca vaccine's safety (compared with the one produced by Pfizer BioNTech) after the thromboembolic events associated with this vaccine candidate, the rate of willingness to vaccinate [87] was sustained even after this published data [116] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, half of the participants indicated that they would receive the vaccine as soon as it became available, while more than one-third preferred delaying receiving it for a few months. In a study that specifically focused on vaccine acceptance according to vaccine type, only 20.9% were willing to receive BNT162b2 [6] , [19] . The acceptance of vaccines in KSA is variable.…”
Section: Discussionmentioning
confidence: 99%
“…The acceptance of COVID-19 among healthcare workers was 70% especially among male HCWs and those who believe in vaccine safety [ 20 ]. Among HCWs, 24.4% were willing to receive the ChAdOx1 COVID-19 vaccine, and 20.9% were willing to receive the mRNA BNT162b2 vaccine [ 21 ]. In the early phase of the enrollment of the mRNA vaccine in KSA, 352 (33.27%) of 1,058 HCWs were enrolled to receive or received the vaccine [ 22 ].…”
Section: Introductionmentioning
confidence: 99%